Bronchial artery embolization combined with left pulmonary resection in the treatment of fibrosing mediastinitis complicated with massive hemoptysis: a case report - Liu, Min; Liu, Jixiang; Chen, Shi; Gao, Xiaoyan; Sun, Lu; Li, Fajiu; Li, Chenghong (Frontiers in Medicine, 2024)
Fibrosing mediastinitis (FM) is a rare and benign fibroproliferative disease that presents with the proliferation of extensive, dense fibrous tissue in the mediastinum. Hemoptysis is a common clinical manifestation of FM. Clinically, most patients exhibit mild to moderate hemoptysis. We report a case of FM complicated with life-threatening massive hemoptysis. The patient was successfully rescued through a combination of bronchoscopic balloon closure, bronchial artery embolization (BAE), and surgical interventions. Although FM is frequently benign, vascular involvement can progress to life-threatening massive hemoptysis and must be treated appropriately.